2018
DOI: 10.1002/ajoc.201800086
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed Bis‐ or Trifunctionalization of Alkynyl Carboxylic Acids: An Efficient Route to Bis‐ and Tris‐selenide Alkenes

Abstract: Ah ighly efficient copper-catalyzed protocolf or the synthesis of bis-and tris-selenide alkenes from alkynyl carboxylic acids and diselenides has been developed. The reaction of alkynyl carboxylic acids and diselenides in the presence of CuI/Cs 2 CO 3 /toluene under white light LEDs only gave bis-selenide alkenes, whereas tris-selenide alkenes were obtained in the presence of aC uI/Cs 2 CO 3 /NMP system. This method provides ar apid access to bis-and tris-selenide alkenes derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 67 publications
0
48
0
Order By: Relevance
“…Some of the 5‐seleno‐triazole products obtained by this decarboxylative coupling cascade show potent inhibitory activities against human gastric cancer. The same group found that in the absence of organoazides, tris‐selenide alkenes are formed [310] . Alkynyl selenides generated from decarboxylative coupling were proposed as intermediates in both cases.…”
Section: Decarboxylative C−chalcogen Bond Formationmentioning
confidence: 96%
“…Some of the 5‐seleno‐triazole products obtained by this decarboxylative coupling cascade show potent inhibitory activities against human gastric cancer. The same group found that in the absence of organoazides, tris‐selenide alkenes are formed [310] . Alkynyl selenides generated from decarboxylative coupling were proposed as intermediates in both cases.…”
Section: Decarboxylative C−chalcogen Bond Formationmentioning
confidence: 96%
“…[190] The synthesis of bis-selenide alkenes 319 and trisselenide alkenes 320 from alkynyl carboxylic acids 318 and diselenides 4 is shown in Scheme 101. [191] The reaction of alkynyl carboxylic acids 318 and diselenides 4 in the presence of CuI/Cs 2 CO 3 /toluene under white light LEDs only gave bis-selenide alkenes 319, whereas tris-selenide alkenes 320 were obtained in the presence of a CuI/Cs 2 CO 3 /NMP (N-methyl-2-pyrrolidone) system. [192][193] The synthesis of mono-selanyl alkene 321 or bisselanyl alkene 322 was successfully achieved in good yields and selectively.…”
Section: Synthesis Of Bis-and Tris-selenide Alkenementioning
confidence: 99%
“…This approach could nicely address the polyselenation of alkynyl carboxylic acids by avoiding the use of electrophilic diselenides. [8] Therefore, we proposed a copper-catalyzed three-component cascade coupling of alkynyl carboxylic acids, Se powder and epoxides (Scheme 1C). As a blueprint of our design, we assumed that copper-catalyzed decarboxylative selenation of alkynyl carboxylic acids with elemental selenium could generate alkynylselenylcopper species.…”
Section: Introductionmentioning
confidence: 99%
“…Given our long‐term interest in the difunctionalization of elemental selenium, [9] we aimed to find a new pathway for the alkylation of alkynylselenyl anions. This approach could nicely address the polyselenation of alkynyl carboxylic acids by avoiding the use of electrophilic diselenides [8] . Therefore, we proposed a copper‐catalyzed three‐component cascade coupling of alkynyl carboxylic acids, Se powder and epoxides (Scheme 1C).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation